2017
DOI: 10.3390/app7070659
|View full text |Cite
|
Sign up to set email alerts
|

A Single Gyroscope Can Be Used to Accurately Determine Peak Eversion Velocity during Locomotion at Different Speeds and in Various Shoes

Abstract: Abstract:Gyroscopes have been used in previous studies to measure the peak angular velocity of the shoe or foot in the frontal plane (evVel). However, it is not clear whether different test conditions (footwear hardness or locomotion speed) can influence the accuracy of evVel. The purpose of the present study was to compare the accuracy of gyroscopes and electrogoniometers when measuring evVel and the time until evVel (t_evVel) in 12 different conditions using a single axis gyroscope attached to the heel cap. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…With the further advancement of sensor technologies and data analyzing techniques, micro-electro-mechanical sensors (MEMS) have become useful tools for biomechanical research and clinical practice [ 1 ]. It has been reported that these wearable motion sensors are an inexpensive alternative to optoelectronic systems and force plates, that they are simple to handle, cost-effective, and are suitable for field measurements [ 2 , 3 , 4 , 5 , 6 ]. When using these sensors, spatio-temporal and kinetic parameters during walking and running can be analyzed in clinical as well as in sportive applications.…”
Section: Introductionmentioning
confidence: 99%
“…With the further advancement of sensor technologies and data analyzing techniques, micro-electro-mechanical sensors (MEMS) have become useful tools for biomechanical research and clinical practice [ 1 ]. It has been reported that these wearable motion sensors are an inexpensive alternative to optoelectronic systems and force plates, that they are simple to handle, cost-effective, and are suitable for field measurements [ 2 , 3 , 4 , 5 , 6 ]. When using these sensors, spatio-temporal and kinetic parameters during walking and running can be analyzed in clinical as well as in sportive applications.…”
Section: Introductionmentioning
confidence: 99%
“…The method of tracking also means that the location of the sensor can be influential in data collection [39]. If there is a need to integrate the sensors with equipment, another consideration to factor will be selecting compatible electronics and locations around those sensors [42].…”
Section: Sensorsmentioning
confidence: 99%
“…Specifically, authors evaluated the efficacy of the considered algorithms in different practical experiment setups where footwear hardness and locomotion patterns were varied. The second paper, 'A Single Gyroscope Can Be Used to Accurately Determine Peak Eversion Velocity during Locomotion at Different Speeds and in Various Shoes' authored by C. Mitschke, M. Öhmichen, and T. L. Milani, introduced a method to measure the frontal plane peak angular velocity during locomotion using a single gyroscope [3].…”
Section: Wearable Computing and Machine Learning For Applications In mentioning
confidence: 99%